Exploring the relative contribution of mineralogy and CPO to the seismic velocity anisotropy of evaporites - Vargas-Meleza, L.; Healy, D.; Alsop, G.I.; Timms, Nicholas Eric (Pergamon-Elsevier Science Ltd., 2015)
We present the influence of mineralogy and microstructure on the seismic velocity anisotropy ofevaporites. Bulk elastic properties and seismic velocities are calculated for a suite of 20 natural evaporate samples, which consist mainly of halite, anhydrite, and gypsum. They exhibit strong fabrics as a result of tectonic and diagenetic processes. Sample mineralogy and crystallographic preferred orientation (CPO) were obtained with the electron backscatter diffraction (EBSD) technique and the data used for seismic velocity calculations. Bulk seismic properties for polymineralic evaporites were evaluated with a rock recipe approach. Ultrasonic velocity measurements were also taken on cube shaped samples to assess the contribution of grain-scale shape preferred orientation (SPO) to the total seismic anisotropy. The sample results suggest that CPO is responsible for a significant fraction of the bulk seismic properties, in agreement with observations from previous studies. Results from the rock recipe indicate that increasing modal proportion of anhydrite grains can lead to a greater seismic anisotropy of a halite-dominated rock.Conversely, it can lead to a smaller seismic anisotropy degree of a gypsum-dominated rock until anestimated threshold proportion after which anisotropy increases again. The difference between thepredicted anisotropy due to CPO and the anisotropy measured with ultrasonic velocities is attributed to the SPO and grain boundary effects in these evaporites.